Heparin: The Journey from Parenteral Agent to Nasal Delivery - Carpenè, Giovanni; Negrini, Davide; Lippi, Giuseppe; Favaloro, Emmanuel J.; Montagnana, Martina (Seminars in Thrombosis and Hemostasis, 2022)
Although the worldwide usage of direct oral anticoagulants has continuously increased over the past decade, heparin remains an important weapon in the current arsenal of anticoagulant drugs. Parenteral heparin administration (i.e., either intravenously or subcutaneously) has represented for decades the only possible route for generating a significant anticoagulant effect, although being notoriously associated with some important drawbacks such as discomfort and risk of low compliance, thus paving the way to searching for more amenable means of administration. We provide here an updated analysis of animal and human studies that have explored the feasibility, suitability, and efficiency of heparin administration through the unconventional nasal route, as a possible alternative to the more traditional parenteral injection. The major hurdles that contribute to impair intranasal absorption and systemic delivery of heparin are represented by its relatively high molecular weight and negative charge. Therefore, although pure drug administration would not be associated with efficient nasal adsorption, or by systemic biological activity (i.e., anticoagulant effect), the combination of low molecular weight heparins and absorption enhancers such as surfactants, mucoadhesive, cyclodextrins, polyethylenimines and encapsulation into (nano)carriers seems effective to at least partially improve drug transport through the nasal route and allow systemic delivery in animals. Besides generating anticoagulant effects, intranasal heparin administration can also produce local pleiotropic effects, mostly related to anti-inflammatory properties, such as attenuating airway allergic inflammation or inhibiting the binding of the spike protein of some coronaviruses (including severe acute respiratory syndrome coronavirus 2) to their host cell receptors. This preliminary evidence represents a valuable premise for planning future studies in humans aimed at establishing the pharmacokinetics and biological activity of locally and systemically delivered intranasal heparin formulations.
Keywords: heparin; low molecular weight heparin; nasal; anticoagulant